PENEGAKAN PIDANA HIDUP BERSAMA DILUAR PERNIKAHAN IMPLIKASI HUKUM TERHADAP KEABSAHAN PERNIKAHAN TIDAK TERCATAT - Siti Nurul Dini Anggraeni; Dey Ravena (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This study analyzes the criminal enforcement of Article 412 of Law Number 1 of 2023 on the Indonesian Criminal Code (KUHP) concerning cohabitation outside marriage. The central issue is the ambiguity in applying this provision to siri marriages that are religiously valid but administratively unregistered under Indonesian marriage law. Using a normative juridical approach with grammatical, systematic, and teleological interpretation, this study finds that Article 412 fails to distinguish between pure cohabitation and siri marriage as a form of living law. This legal inconsistency undermines legal certainty and grants excessive judicial discretion, potentially leading to disparities in court decisions. The criminalization of such conduct also raises concerns regarding civil status, inheritance rights of children, and the constitutional right to privacy. Based on Ashworth’s Test of Criminalization, the enforcement of Article 412 is disproportionate and inconsistent with the harm principle and the doctrine of ultima ratio.